Effect of different concentrations of benzyladenine and frequency of watering on growth and quality of Dracaena sanderiana and Codiaeum variegatum - Fuadi, Misril; Tengku Muda Mohamed, Mahmud; Salleh, N. S.; Anwar, Md. Parvez; Awang, Yahya; Ramlan, Mohd Fauzi (Triveni Enterprises, 2014)
The effect of benzyladenine concentration and watering frequency on the growth and quality of Dracaena sanderiana and Codiaeum variegatum was evaluated. Plants were treated with different benzyladenine concentrations of (0, 75, 150, 225 or 300 mg l-1) and watering frequencies, daily, every 4, 7 or 10 days interval. Benzyladenine concentration and watering frequency interacted significantly for plant grade on both species. This interaction resulted in the highest grade at 225 mg l-1 benzyladenine and daily watering for D. sanderiana and 150 mgl-1 benzyladenine and daily watering for C. variegatum. No significant interactions between benzyladenine concentration and watering frequency were observed for photosynthesis rate, stomatal conductance, specific leaf area and fresh weight of either species. For D. sanderiana, the highest photosynthesis rate (5.70 mmolm-2s-1) occurred at 225 mg l-1and decreased with increasing watering frequency. For C. variegatum, the highest photosynthesis rate (4.49 mmolm-2s-1) was recorded with benzyladenine concentration of 150 mg l-1, and photosynthesis rate was found independent of watering frequency. For both species, stomatal conductance was recorded highest at 225 mg l-1, but watering frequency failed to influence stomatal conductance. For better quality, D. sanderiana should be sprayed with benzyladenine at 225 mg l-1, and C. variegatum with benzyladenine at 150 mg l-1 in combinations with watering at 4 days interval.